CHANGES IN THE WEIGHT OF RAW COTTON IN ONE BOX IN VARIETARY COTTON HYBRIDS - Juraev S.T. (Journals Park Publishing, 2022)
A comparative analysis of the mass of raw cotton in one boll was carried out in 4 hybrid combinations of cotton, with an enriched genetic basis in three regions of Uzbekistan. The proportion of the influence of genotype and environmental factors on the manifestation of the trait has been established. Among modern methods that make it possible to achieve an increase in the effectiveness of selection, the use of various ecological and geographical zones is becoming more widespread.
Keywords: cotton, raw cotton weight per boll, adaptive selection, introgressive forms, dispersion.